Smart Grid Digital Forensics Investigation Framework - Mohd Abdullah H.I.; Mustaffa M.Z.; Rahim F.A.; Ibrahim Z.-A.; Yusoff Y.; Yussof S.; Bakar A.A.; Ismail R.; Ramli R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power transmission networks; Electronic crime countermeasures; Grid computing; Knowledge based systems; Smart power grids; Computing environments; Forensics investigations; Grid operation; Internal operations; Knowledge base; Security vulnerabilities; Smart grid; Stuxnet; Digital forensics